The Occurrence and Possible Aetiology of Spondylolysis in a Pre‐contact California Population. (17th April 2012) - Pilloud, M. A.; Canzonieri, C.
ABSTRACT The occurrence of spondylolysis (neural arch separation at the pars interarticularis) is reported in a pre‐contact (720–550 Cal BP) Central California population, CA‐CCo‐647 (n = 46). Spondylolysis was examined within this population to assess differences in sex, age, and possible relationships with biological affinity. Furthermore, prevalence rates of spondylolysis were compared across various populations to discern the aetiology of the defect. Within CA‐CCo‐647, spondylolysis was found in 17.4% (8/46) of the population. All occurrences are complete, bilateral separations of the neural arch in the lower lumbar (L4 and L5). The defect is not seen in individuals below the age of 18, and there is no correlation between adult age and spondylolysis. Male individuals display the defect at a higher rate (30.8% ‐ 4/13) than female individuals (12.1% ‐ 4/33); however, this is not a statistically significant finding. There does seem to be a correlation between an individual's sex and the onset of the defect; male individuals display spondylolysis at a younger age than female individuals. This finding could represent differences in activity patterns among young male and female individuals. In a biological distance analysis using craniometric data, male and female individuals with spondylolysis clustered closely, suggesting a genetic component for the defect. Finally, significant differences were found in spondylolysis prevalence between various populations representing distinct geographic and temporal settings. Significant differences were found among Native pre‐contact samples and even between two comparable pre‐contact California skeletal samples. These populations all engaged in distinct activities and were likely composed of genetically distinct groups of individuals, which may account for the differences in spondylolysis prevalence. All of these findings, both within CA‐CCo‐647 and between the various samples, suggest that the aetiology of spondylolysis is likely an interaction of genes and activity. Copyright © 2012 John Wiley & Sons, Ltd.